Embedded system application development on raspberry Pi 3 : smart home safety and alert system for elderly (elderwise) - Choong, Wen Jun (2019)
With the advent of the Fourth Industrial Revolution, a change in the way we live and relate to one another is dawning, opening up a new world into the Internet of Things. Smart home systems are becoming increasingly popular, with aims to improve quality of life and bring convenience into homes. However, such smart home systems are usually costly and limited in functionality. This project looks into the design of a smart home system for the elderly with the use of the low-cost but high-performing Raspberry Pi 3, as well as the free, open-source Telegram application. The system provides alert, monitoring and voice assistant functionalities for elders left alone at home, which creates a safer environment in the event of a fall. These functionalities would be further discussed in detail.